Evaluación de estudiantes de posgrado en ciencias de la salud. - ARENIS OLARTE, YURY; ELIZABETH PINILLA, ANÁLIDA (Acta Medica Colombiana)
This article visualizes by metasynthesis studies and pedagogical scopes the assessment of postgraduate students. It starts contextualizing the paradigmatic changes that the evaluation has taken at different levels of education, focusing on higher education, more precisely in the teaching / evaluation / learning in health sciences. Epistemological, axiological and methodological view of the evaluation is extended, so that it is understood as a complex process, contextualized, comprehensive and multi-relational of professional competences with a diagnosis purpose, educational, of feedback and self-regulation for its improvement. At postgraduate level, the literature shows that the processes of teaching - learning and research should be directed to the development of professional competences, and in turn, the evaluation process is structured in them according to new pedagogical approaches, so that the evaluation is support for the learning and the integral formation of a postgraduate student. In postgraduate programs in health sciences, professional competences include generic or transversal and specific competences, which have dimensions that are developed in a progressive way. According to Miller’s pyramid, for developing a competence, a student advances through different dimensions: know how to recognize, know how to do or know how, know undertake and know to be. So, it is essential to consider the pyramid of each professional competence, updating the concept of evaluation as an axis process for learning and teaching, all these framed in a pedagogical model to guide the focus of the curriculum which define what is evaluation, what should be assessed, how to assess and what to assess. Deepening more in the complexity of the evaluation, it is necessary to understand how an instrument should be appropriate to a dimension or different dimensions to assess professional competence; in postgraduate programs of health sciences, new techniques and evaluation instruments such as: learning portfolio or portfolio, objective structured clinical evaluation (OSCE), the rubrics, exercise reduced clinical examination (Mini CEX), among others, can be used. Therefore, it is necessary to rethink the educational paradigm and use relevant tools for the desired professional competences that are going to be evaluated, which must be contextualized and linked to a professional situation to succeed not only in the evaluation process but in the formation of future graduates. Therefore, elements are provided for teachers to think on their role as evaluators so that the evaluation may enrich teachers and students rather than cause them conflict at various levels and stages.